EVALUASI PROGRAM BESTRA (BERSIH – SOPAN – TERTIB – RAPI – AMAN) DI SEKOLAH DASAR DENGAN MENGGUNAKAN MODEL GOAL FREE EVALUATION - Angely, Gabriela Afra; Mawardi, Mawardi (Universitas Negeri Medan, 2024)
This study aims to evaluate the BeSTRA program at SD Kristen Lentera Ambarawa using a goal-free evaluation model. This research uses a qualitative approach with an evaluation method. Data collection techniques use document studies, observations, and interviews. The subjects of the study data included the principal, the vice principal for student affairs, three teachers, and fifteen students in grades 4, 5, and 6. Data analysis techniques use the Miles and Huberman model which includes data reduction, data presentation, and conclusions. The results showed that the planning and implementation of the BeSTRA program were by the BeSTRA cultural guidelines at Lentera Ambarawa Christian Elementary School for the 2023/2024 academic year. The supporting factors of the BeSTRA program are cooperation between school residents and the habituation of the BeSTRA program implementation schedule. The positive impact of the BeSTRA program is to form a clean, polite, orderly, neat, and safe character in students as a habit or habit in everyday life, and create a clean and comfortable environment to live in. However, on the other hand, there are inhibiting factors that become obstacles to the BeSTRA program, namely the lack of time and responsibility of students in implementing the BeSTRA program in schools.